Pengaruh Kualitas Layanan dalam Menciptakan Kepuasan Publik di Kantor Pelayanan Publik, Jakarta Utara - Janny Rowena; Fuji Rahayu Wilujeng; Glisina Dwinoor Rembulan (JIEMS (Journal of Industrial Engineering and Management Systems), 2020)
One indicator that shows the quality of government performance is the quality of public service offices. Public services in Indonesia have an important role in economic and political life. The magnitude of the role of the district office in providing services around population bureaucracy issues, especially in the province of DKI Jakarta, is still often getting complaints from the public. This study aims to assess the level of community satisfaction with the quality of district office services in the Jakarta province, specifically the North Jakarta municipality. This study uses multilinear regression and uses the T-test to find out the significant level of influence of independent variables on the dependent. The study used five exogenous variables (procedures, information, time, facilities, and infrastructure, and environmental comfort) and 1 endogenous variable (satisfaction). The results of this study are all exogenous variables that have a positive and significant effect on the satisfaction of Jakarta citizens, which means that urban district office services have a positive and significant effect on the satisfaction of Jakarta citizens when viewed from procedures, information, time, facilities, and infrastructure as well as environmental comfort. The provincial government of DKI Jakarta must maintain and improve existing service procedures, some attributes of information that are already very good, good values regarding the certainty of the time of completion of services, several aspects of facilities and infrastructure, and comfortable environmental conditions, both in the service office or in the service support facilities.